Predictive value of screening for rapid hiv testing in health facilities. Huánuco - 2012 - Melgarejo Figueroa, María (2017)
The investigation’s fundamental purpose, it was focused to determine the Valor Predictivo of tamizaje’s spot tests in order to VIH;Descriptive investigation epidemiologic, retrospective and transverse; The basic procedures, 2009, 2010 and 2011 came true with the epidemiologic statistics in the sensibility and specificity tests of the years; The more important findings went than: This procedure had great acceptance for part of los/las users, since they surpassed them 33,000 you show in solidum group poblacional and tendency was maintained during the three years, referring to the sensibility average he was equivalent to the 100; Finally we come to an end than tamizaje’s spot tests in order to VIH, they have Value Predictivo Positivo, applied to the population that he proceeded to Salud’s Establishments in the Region Huánuco.